2004
DOI: 10.1038/sj.embor.7400083
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of HAP46/BAG‐1

Abstract: HAP46/BAG-1M and its isoforms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
0
17
1
4
Order By: Relevance
“…Similar experiments were performed to address the role of CHIP, BAG-1, BAG-3 and BAG-6 in DRiPs processing and antigen presentation. Surprisingly, depletion of CHIP or BAG-1 had no effect on the level of SL8 presentation, suggesting that these two previously characterized enhancers of proteasome degradation 29,40 interact with a different set of misfolded HSPA8 clients than GFP-SL8 DRiPs (Fig. 5F).…”
Section: Do Not Distributementioning
confidence: 93%
See 1 more Smart Citation
“…Similar experiments were performed to address the role of CHIP, BAG-1, BAG-3 and BAG-6 in DRiPs processing and antigen presentation. Surprisingly, depletion of CHIP or BAG-1 had no effect on the level of SL8 presentation, suggesting that these two previously characterized enhancers of proteasome degradation 29,40 interact with a different set of misfolded HSPA8 clients than GFP-SL8 DRiPs (Fig. 5F).…”
Section: Do Not Distributementioning
confidence: 93%
“…Ubiquitination of misfolded HSPA8 clients involves the E3 ligase CHIP, 6 and is modulated by co-chaperones of the Bcl-2-associated athanogene (BAG) family, although the precise role of HSPA8 and these associated molecules in DRiPs processing and subsequent MHCIrestricted presentation has not been extensively addressed. 36,37 BAG proteins have been reported to facilitate the degradation of Hsp70/HSPA8 substrates by the proteasome or through autophagy, 7,29,[38][39][40][41] and are therefore likely to also participate in the quality control mechanisms regulating GFP-SL8 DRiPs folding and degradation. We silenced different mRNAs coding for HSPA8 42 and associated BAG co-chaperones.…”
Section: Do Not Distributementioning
confidence: 99%
“…Several studies have found increased expression of Hsp70 in various hormone-treated cell types (Tang et al, 1995;Jones et al, 2000;Lu et al, 2002;Gehring, 2004). The fact that Hsp70 can completely prevent iA␤ 1-42 -mediated toxicity indicates only that Hsp70 is sufficient for neuroprotection against iA␤ 1-42 toxicity but does not rule out the possibility that other effects of the steroid hormones on neurons could also be neuroprotective.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects have indeed been observed by several research groups using different experimental systems (reviewed by Alberti et al 2003;Gehring 2004). The prevalence of interactions with mammalian Hsp70 molecular chaperones is the reason why Hap50/BAG-1L, Hap46/BAG-1M, and isoforms have been called cochaperones.…”
Section: Interaction With Hsp70 Molecular Chaperonesmentioning
confidence: 80%
“…In particular, Hap50/BAG-1L is often expressed at rather high levels in various tumors compared with normal cells. Even more importantly, the cochaperones Hap50/BAG-1L and Hap46/BAG-1M could serve in the future as molecular targets for therapeutic approaches, as has been discussed, for example, in reviews by Gehring (2004), Sharp et al (2004), and Townsend et al (2005), and it will be very helpful for the treatment of some cancer types if the cellular levels of Hap50/BAG-1L and Hap46/ BAG-1M could be lowered by specific drugs. In addition, molecular chaperones themselves play a role in carcinogenesis and are hoped to soon become available for pharmacological interventions (Jäättelä 1999;Mosser and Morimoto 2004).…”
Section: Further Directions Of Researchmentioning
confidence: 99%